Donbas crisis key actors: narratives and perceptions in the interviews of Ukrainian elites - Velivchenko, Viktor (Cognition, Communication, Discourse, 2019)
This article examines real events, their perceptions and narratives concerned with the key actors in the Donbas crisis – Ukraine, the EU/EU member states, Russia and the USA. Perceptions and narratives are traced in the texts of interviews with Ukrainian policy- and decision-makers from political, business, cultural, and civic cohorts (40 respondents). The elites were interviewed in the winter of 2016 within the framework of the Jean Monnet Network “Crisis, conflict and critical diplomacy: EU perceptions in Ukraine and Israel/Palestine” (C3EU), supported by Earsmus+ program of the European Commission. Informed by the strategic narrative theory [Miskimmon et al. 2013], the article undertakes a qualitative content analysis of the interview texts, explicating elite perceptions of the crisis in Donbas. The results spell the need for a more nuanced understanding of Ukraine’s perceptions of key actors in the ongoing conflict as well as the origin of these perceptions. Arguably, such understanding may benefit the EU’s critical diplomacy towards Ukraine and add a valuable insight to the constructive dialogue between Ukraine and the EU.